ralucaalexandra2
10

# 13 . Gasiti solutia pentru fiecare ecuatie : a) 2(5x-3)+4x+3(2x-7)=5(3x+1)+8. b)5(2x-3)+3(5x-6)+13=8(3x+7)-63 c)7(4x-3)-4(3x+8+25=3(4x+9)-43 d)3(4x-5)-3(2x+7)+32=2(2x+1)-14 e)6(x+3)+3x+2(2x+5)=3(x+1)-5 f)3(2x-1)+4(x+2)-15=5(x+1)+35 g)5(3x+4)+3(5x+6)-28=7(4x+9)-47.

(2) Răspunsuri
andreialexandru5

a) 2(5x-3)+4x+3(2x-7)=5(3x+1)+8. 10x-6+4x+6x-21= 15x+5+8 10x+4x+6x-15x= 13+6+21 5x= 40⇒ x= 40:5= 8 b)5(2x-3)+3(5x-6)+13=8(3x+7)-63 10x-15+15x-18+13= 24x+56-63 10x+15x-24x= -7+15+18-13 x= 13  c)7(4x-3)-4(3x+8)+25=3(4x+9)-43 28x-21-12x -32+25= 12x+27-43 28x-12x-12x= 27-43+21+32-25 4x= 12⇒ x= 12:4 =  3   d)3(4x-5)-3(2x+7)+32=2(2x+1)-14 12x-15-6x-21+32= 4x+2-14 12x-6x-4x= -12+15+21-32 2x= -8⇒ x= -8:2= -4  e)6(x+3)+3x+2(2x+5)=3(x+1)-5 6x+18+3x+4x+10= 3x+3-5 13x-3x= -2-18-10 10x= -30⇒ x= -30:10= -3 f)3(2x-1)+4(x+2)-15=5(x+1)+35 6x-3+4x+8-15= 5x+5+35 10x-5x= 40+3-8+15 5x= 50⇒ x= 50:5= 10 g)5(3x+4)+3(5x+6)-28=7(4x+9)-47.   15x+20+15x+18-28= 28x+63-47 30x-28x= 16-20-18+28 2x= 6⇒ x= 6:2= 3

Safiye

a) 2 ( 5x - 3 ) + 4x + 3 ( 2x - 7 ) = 5 ( 3x + 1 ) + 8 10x - 6 + 4x + 6x - 21 = 15x + 5 + 8 20x - 15 x = 13 + 6 + 21 5x = 40 x = 40 : 5 x = 8 b) 5 ( 2x - 3 ) + 3 ( 5x - 6 ) + 13 = 8 ( 3x + 7 ) - 63 10x - 15 + 15x - 18 + 13 = 24x + 56 - 63 25x - 24x = -7 + 15 + 18 - 13 x = 13 c) 7 ( 4x - 3 ) - 4 ( 3x + 8 ) + 25 = 3 ( 4x + 9 ) - 43 28x - 21 - 12x - 32 + 25 = 12x + 27 - 43 16x - 12x = -16 + 21 + 32 - 25 4x = 12 x = 3 d) 3 ( 4x - 5 ) - 3 ( 2x + 7 ) + 32 = 2 ( 2x + 1 ) - 14 12x - 15 - 6x - 21 + 32 = 4x + 2 - 14 6x - 4x = - 12 + 15 + 21 - 32 2x = -8 x = - 4 e) 6 ( x + 3 ) + 3x + 2 ( 2x + 5 ) = 3 ( x + 1 ) - 5 6x + 18 + 3x + 4x + 10 = 3x + 3 - 5 13x - 3x = - 2 - 18 - 10 10x = -30 x = -3 f) 3 ( 2x - 1 ) + 4 ( x + 2 ) - 15 = 5 ( x + 1 ) + 35 6x - 3 + 4x + 8 - 15 = 5x + 5 + 35 10x - 5x = 40 + 3 - 8 + 15 5x = 50 x = 10 g) 5 ( 3x + 4 ) + 3 ( 5x + 6 ) - 28 = 7 ( 4x + 9 ) - 47 15x + 20 + 15x + 18 - 28 = 28x + 63 - 47 30x - 28x = 16 - 20 - 18 + 28 2x = 6 x = 3